Perilaku Beralih Merek Dalam Pembelian Kartu Seluler Prabayar - Widyatmoyo Widyatmoyo (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2010)
Brand switching behavior is important issue in hard business competition nowadays, especially in cellular phone business. Brand switching behavior is defined as consumer susceptibility to switch to other brand because of several reasons.    This research’s purposes are: 1) to analyze prior experience, product knowledge and media search factors in order to shape the customer’s consideration set size in buying SIM card, 2)to analyze influence of customer satisfaction to brand switching behavior in buying SIM card, 3)to analyze  influence of consideration set size to brand switching behavior in buying SIM card, 4)to analyze influence of retailer search to brand switching behavior in buying SIM card. The sample of research is 159 respondents fulfilling the criteria as people who lived in Yogyakarta Special Region and have switched their SIM card in last 3 years. The research data are primary data, that are straight taken from questionnaires have been given to respondents. Validity test uses confirmatory factor analysis and reliability test uses alpha cronbach. Data analyze uses stuctural equation model (SEM) with AMOS program. Research model in this research is model that was developed by Sambandam and Lord (1995).